Intalasi Komputer Dan Penggunaan E-Info Pada SMA N 1 Kefamenanu - Claria Fransiska Agatha Berek; Siprianus Septian Manek (Bakti Cendana, 2019)
Information and communication technology has now developed rapidly in community, especially among students. However, there are still many who have not been able to utilize it properly, such as the problem that occurred in SMAN 1 Kefamenanu. Utilization of information and communication technology in this school has not been maximized due to facilities and infrastructure in the computer laboratory in SMAN 1 Kefamenanu. There are still a number of damaged computers or operating systems that have not been installed. From the problems above, the service activity was carried out with the title Computer Installation and Use of E-Info at SMAN 1 Kefamenanu. The results of the community service activities were: the use of computer laboratory becomes more maximal and with the introduction of the use of e-info to students, so students can apply the use of information and communication technology in the teaching and learning process in SMAN Kefamenanu.